Sorption of Cadmium(II) from Aqueous System by Using Bicarbonate Impregnated Sulphuric Acid Treated Pongamia pinnata Seedpod Carbon - Senthil, M.; Arulanantham, A. (Asian Journal of Chemistry, 2010)
The adsorption of Cd(II) on modified bicarbonate impregnated sulphuric acid treated Pongamia pinnata activated carbon (BSPAC) prepared from its seedpods was investigated. The maximum adsorption was observed as a function of solution pH, contact time, carbon dosage and initial metal ion concentration. The adsorption capacity of adsorbent for cadmium was obtained by using Freundlich, Langmuir and Temkin isotherms. Kinetic studies were made with pseudofirst- order, pseudo-second-order and reversible-first-order kinetic equations. The results were compared with commercially available activated carbon (CAC) of 20-50 ASTM mesh size.